2016
DOI: 10.1007/978-1-4939-3512-3_27
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for Photoreceptor Engineering

Abstract: Sensory photoreceptors underpin optogenetics by mediating the noninvasive and reversible perturbation of living cells by light with unprecedented temporal and spatial resolution. Spurred by seminal optogenetic applications of natural photoreceptors, the engineering of photoreceptors has recently garnered wide interest and has led to the construction of a broad palette of novel light-regulated actuators. Photoreceptors are modularly built of photosensors that receive light signals, and of effectors that carry o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Importantly, the N and C termini of LOV2 are oriented towards the same direction making it suitable to insert into other proteins [41][42][43], and in the case of PKM2, into the HLH region. Furthermore, LOV2 is suitable for use in mammalian cells [44], which tolerate blue light well and do not need exogenous cofactors because they produce FMN from dietary vitamin B. Altogether, we concluded that LOV2 is a suitable domain to insert into PKM2 and potentially regulate its activity and for subsequent use in mammalian cells.…”
Section: Molecular Dynamics Simulations Identify Conformational Changmentioning
confidence: 73%
“…Importantly, the N and C termini of LOV2 are oriented towards the same direction making it suitable to insert into other proteins [41][42][43], and in the case of PKM2, into the HLH region. Furthermore, LOV2 is suitable for use in mammalian cells [44], which tolerate blue light well and do not need exogenous cofactors because they produce FMN from dietary vitamin B. Altogether, we concluded that LOV2 is a suitable domain to insert into PKM2 and potentially regulate its activity and for subsequent use in mammalian cells.…”
Section: Molecular Dynamics Simulations Identify Conformational Changmentioning
confidence: 73%
“…Phototropins, cryptochromes, and blue light using flavin adenine dinucleotide (BLUF) proteins each bind a flavin derivative as a chromophore that undergoes covalent bond formation with a cysteine residue, electron transfer (ET), and proton-coupled electron transfer (PCET), respectively, during the photocycle. Understanding the fundamental mechanisms of naturally occurring photoreceptor proteins is important for engineering novel systems that use light as a tool to achieve noninvasive control of biological processes with high spatiotemporal resolution (5)(6)(7).…”
mentioning
confidence: 99%
“…Engineering of optogenetic tools requires not only successful control of an effector domain with a photoreceptor but also optimizations to enhance the tool performance. 3,4 An often used photoreceptor for development of optogenetic tools is the light oxygen voltage (LOV) domain 2 of plant phototropins. 5 This photoreceptor binds to the flavin mononucleotide (FMN), which is primarily responsible for light perception.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Modern methods of genetic engineering facilitate implementation of a tool into the genome of host cells. , Optogenetic tools have a dual functionality; a photoreceptor part perceives the light signal, and an effector domain induces a specific response. Engineering of optogenetic tools requires not only successful control of an effector domain with a photoreceptor but also optimizations to enhance the tool performance. , …”
Section: Introductionmentioning
confidence: 99%